2015
DOI: 10.1088/1674-1056/24/4/047501
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory and frequency of vortex gyration in a multi-nanocontact geometry

Abstract: Nonlinear vortex gyrotropic motion in a three-nanocontacts system is investigated by micromagnetic simulations and analytical calculations. Three out-of-plane spin-polarized currents are injected into a nanodisk through a centered nanocontact and two off-centered nanocontacts, respectively. For current combination (i p1 , i p0 , i p2 ) = (−1, 1, −1), the trajectory of the vortex core is a peanut-like orbit, but it is an elliptical orbit for (i p1 , i p0 , i p2 ) = (1, 1, −1). Moreover, the gyrotropic frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For the thin disk with L = 15 nm, the eigenfrequency first increases with j increasing and it turns a constant with j further increasing, and the thinner disk has similar dependence of eigenfrequency on the j as demonstrated in our previous study. [22] However, the eigenfrequency first increases and then decreases with j further increasing, which is a peculiar dynamical phenomenon in thicker disks. Figure 3(b) illustrates the dependence of eigenfrequency on current density j in nanodisks with the same thickness.…”
Section: Simulation Details and Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…For the thin disk with L = 15 nm, the eigenfrequency first increases with j increasing and it turns a constant with j further increasing, and the thinner disk has similar dependence of eigenfrequency on the j as demonstrated in our previous study. [22] However, the eigenfrequency first increases and then decreases with j further increasing, which is a peculiar dynamical phenomenon in thicker disks. Figure 3(b) illustrates the dependence of eigenfrequency on current density j in nanodisks with the same thickness.…”
Section: Simulation Details and Resultsmentioning
confidence: 96%
“…[20,21] Furthermore, our research found that the position and the size of point-contact can control the eigenfrequency of MV gyration. [15,22,23] Taking into account the previous studies and considering the better application of MV, [24] we particularly focus on the MV gyration in permalloy (Py) nanodisks with different sizes in this paper and investigate the effects of the point-contact position on MV gyration, including the critical current density of MV gyration, eigenfrequency, trajectory, velocity, and the time for a magnetic vortex to obtain the steady gyration.…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] We found that the trajectory and frequency of VC were also influenced by the current direction and distance. [35,36] These studies inspired us to design a new model to study the VC switching, where the out-of-plane spin-polarized currents are injected through a three-nanocontact geometry with tunable center-to-center distance and different current directions to make a nonuniform system, making it easier to excite the VC to switch with shorter time and less current density.…”
Section: Introductionmentioning
confidence: 99%